Optimal operation of urban tidal drainage pumping station based on genetic algorithm coupled with head-water level successive approximation - Yi, Gong; Wenhao, Zou (Frontiers in Energy Research, 2023)
Aiming at solving optimization scheme for urban tidal drainage pumping stations during heavy rainfall below urban drainage design standard, and problems such as the mismatch between head and water level of pumping stations at each divided time period during solution process, a nonlinear mathematical model for optimal operation of urban tidal drainage pumping station was constructed which took minimal operation cost of station during given operating period as study target, and blade angle of each pump unit in each time period as decision variables with constraints of total water quantity of target drainage, matched motor power of each pump unit, water level of in the drainage area, number of switches and the shortest operation time of pump unit. For the problem of head-water level mismatch at each divided time period of pumping station, genetic algorithm coupled head-water level successive approximation was proposed, which realized matching of river network water level and pumping station operating head. Taking Guazhou Pumping Station in Yangzhou City encountering 10% frequency designed rainfall as an example, optimization schemes under typical working conditions which included different starting drainage water levels and peak-valley electricity prices were obtained, as well as influence of electricity price of divided time period, average head of each divided time period and inflow on the optimization scheme were carried out. Unit optimal operation drainage cost of Guazhou Pumping Station is 45.46 and 51.32 yuan / 104 m3 respectively when starting drainage water level is set as 4.8 m and 4.6 m, which has the corresponding operation benefit of 15.34 % and 4.40 % less than that of conventional operation, and water level variation of river network has dropped 6.61 % and 7.85 % than that of conventional operation. Constructed optimal operation model of urban tidal drainage pumping station and proposed solution method can effectively improve matching degree of pumping head and water level variation, and effectively make a compromise of economic operation of drainage pumping station and safety requirements of water level control of river network in drainage area. Obtained optimization schemes can offer decision-making reference for relevant management departments of drainage pumping stations.